Impact of ChatGPT Usage on Vocational Students’ Critical Thinking: A Conceptual Framework - Syarif, Ahmad (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study explores the impact of ChatGPT usage on vocational students' critical thinking skills, particularly within the context of Indonesian vocational schools. With the rapid development of AI technologies, particularly ChatGPT, this research investigates how its integration into the education system can either enhance or hinder the development of critical thinking. The study employs a qualitative approach with literature review and utilizing small surveys administered to both teachers and students, to gather insights on how ChatGPT influences students' ability to analyze, evaluate, and make decisions. The findings suggest that while ChatGPT has the potential to foster critical thinking by providing tools for in-depth analysis and information synthesis, there is also a risk of over-reliance on AI-generated responses. This study highlights the importance of managing the use of ChatGPT to ensure that students continue to develop independent critical thinking skills, which are crucial for vocational students preparing to enter the workforce. The conceptual framework presented offers a foundation for future research on the integration of AI in education and its effects on cognitive skills development.